Analisis Pengaruh Penerimaan Petugas Rekam Medis Terhadap Penggunaan Rekam Medis Elektronik di Rumah Sakit Indriati Solo Baru - EVA AZZAHRA; Wahyu Ratri Sukmaningsih; Canggih Ajika Pamungkas (MEDIKA TRADA, 2026)
Electronic Medical Records are a health information system whose implementation is mandatory in all healthcare facilities in Indonesia in accordance with Minister of Health Regulation No. 24 of 2022. The success of EMR implementation is determined not only by the technology used but also by user acceptance of the system. This study aims to analyze the influence of medical records staff acceptance on the use of EMR at Indriati Solo Baru Hospital based on the Technology Acceptance Model (TAM) approach. The study used a quantitative method with a cross-sectional design. The study sample consisted of 45 medical records staff selected using total sampling. Data collection was conducted using a Likert-scale questionnaire and analyzed using the Chi-Square test and Fisher’s Exact Test. The results showed that the majority of respondents were female (62.2%), aged 20–30 years (71.1%), held a D3 degree (91.1%), and had 1–5 years of work experience (51.1%). EHR usage was in the optimal category for 25 respondents (55.6%). The analysis results showed that perceived benefits (sig. = 0.473), perceived ease of use (sig. = 1.000), and intention to use (sig. = 0.473) did not have a significant effect on RME usage. Meanwhile, attitude had a significant effect on RME usage (sig. = 0.037). It was concluded that attitude is a factor influencing RME usage at Indriati So Hospital.